Relatório de estágio curricular supervisionado em medicina veterinária - área de bovinocultura de corte - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This report describes the activities developed during the Supervised Curricular Internship in Veterinary Medicine (ECSMV), which was carried out in the Beef Cattle Reproduction area. The activities were carried out at the company Geneplan - Reproduction Bovine, headquartered in the city of Campo Grande, geographically located in the central region of the state of Mato Grosso do Sul. The ECSMV was developed between January 15th to April 15th, 2018, making a total 480 hours, under the supervision of Veterinary Doctor Igor de Mello Cavalheiro and guidance from Professor Fernando Silveira Mesquita. The activities developed consisted of management, planning and execution of the reproduction of beef cattle, with emphasis on Artificial Insemination in Fixed Time (IATF). Specifically, it was possible to monitor the logistical organization of lots of farmed animals and their management for IATF protocols, pregnancy diagnosis by ultrasound, resynchronization and puberty induction in heifers.
Supervised internship report on veterinary medicine - beef cattle area
Keywords: Medicina Veterinária; Clínica veterinária; Reprodução animal; Bovinos; Bovinocultura de corte; Bovinos de Corte; Clínica de grandes animais; Clínica médica veterinária; Veterinary medicine; Veterinary clinic; Animal reproduction; Cattle; Beef Cattle; Large Animal Clinic; Veterinary medical clinic; CNPQ::CIENCIAS AGRARIAS